A study on consumer behavior towards online shopping (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The digital revolution has fundamentally reshaped the landscape of retail, propelling online shopping from a novelty to a dominant force. This shift has triggered a profound change in consumer behavior, demanding a deeper understanding of the factors that drive online purchasing decisions. This article explores the intricacies of consumer behavior towards online shopping, examining the motivations, influences, and evolving trends that define this dynamic marketplace. One of the primary drivers of online shopping's popularity is convenience. Consumers are drawn to the ability to browse and purchase products from the comfort of their homes, at any time of day. This 24/7 accessibility, coupled with the elimination of geographical limitations, expands product selection and streamlines the shopping process. Furthermore, the ability to compare prices and read reviews instantaneously empowers consumers with greater control over their purchasing decisions. Price sensitivity plays a significant role in online shopping behavior. The online marketplace fosters intense competition, leading to frequent discounts, promotions, and price comparisons. Consumers are increasingly adept at utilizing online tools to find the best deals, often prioritizing affordability over brand loyalty. This price-conscious behavior is further amplified by the ease of access to coupon codes and cashback offers, incentivizing online purchases.